Research on the Storage Stability and Coating Salt Spray Resistance Property of Graphene - Modified Zinc Powder Epoxy Primer - GAO Meng, PAN Wei - chao, XU Xiao - rong, HAO Zi - tao, WANG Shu - chuan (Cailiao Baohu)
Aiming at exploring the stability and corrosion resistance changes of graphene - modified zinc powder primer after long - term storage,graphene-modified zinc powder epoxy coatings were prepared with graphene powders obtained by different methods. After long - term storage, the isolated graphene were analyzed by Raman spectrum, transmission electron microscope and scanning electron microscope. The corrosion resistance of graphene - modified zinc powder primer was evaluated by neutral salt spray test (NSS). Results showed that under the reasonable formula of zinc powder primer, with comparing graphene powders prepared by deflagration method and oxidation - reduction method, the graphene - modified zinc powder primer using the former powders possessed better salt spray resistance and better stability.